Curating a connected community in virtual space: Solomon Islands Research Mentoring Tok Stori - Sanga, Kabini; Reynolds, Martyn; Malefoasi, Ambrose; Paulsen, Irene (The Australian Journal of Indigenous Education, 2023)
This article examines the relationship between academic mentoring and tok stori, a Melanesian orality, in a digital environment. This relationship is significant where dispersal is an unintended consequence of the way development aid intersects with academic opportunities for scholars from less developed countries, and, consequently, country-focused academic communities remain undeveloped as education becomes individualised. This situation occurs despite the fact that the self is social and education is a common good in many contexts, such as Solomon Islands in Melanesia. Using the contributions of participants in the Solomon Islands Research Mentoring Tok Stori (SIRMT), we discuss the various kinds of support and outcomes that become possible when deliberate attempts are made to create a connected community through mentoring in virtual space. Among the findings are the significance of mentorship to personal and academic growth, the potential of deliberate community building through virtual means in Solomon Islands and virtual tok stori as a catalyst to developments the physical world.